Rapidly Growing Mycobacterium tuberculosis in the Form of Empyema Necessitans: A Case Report. (August 2022) - Chang, Stephanie H.; Choe, June; Ghandehari, Sara; Chaux, George E.; Chung, Alice P.; Ramzy, Danny; Megna, Dominick J.; Falk, Jeremy A.; Zakowski, Phillip C.
We present a case of rapidly growing disseminated Mycobacterium tuberculosis (MTB) that presented as an empyema necessitans (EN) in a 65-year-old woman with a single right lung transplant admitted for progressive dyspnea. While hospitalized, she had daily fevers and was found to have a right-sided chest wall abscess and pleural effusion. Acid-fast bacilli cultures from the abscess and pleural fluid grew MTB within 4 and 6 days, respectively. Blood cultures later grew MTB as well. Upon initiation of rifampin, isoniazid, pyrazinamide, and ethambutol, she developed hemorrhagic pancreatitis and distributive shock secondary to antituberculosis medications and disseminated MTB. Noteworthy features of this case include the rapid rate of MTB culture growth in less than a week, the development of a likely donor-derived MTB EN, and the clinical challenges of MTB screening and MTB infection management in a solid organ transplant recipient.